A Study of Emotional Intelligence and Teacher Stress among B.Ed Teachers (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
This paper was designed to investigate the relationship between Emotional Intelligence and Stress among B.Ed teachers. To conduct the study, 50 teachers from various B.Ed colleges in Jalandhar by non-probability purposive sampling were selected as sample of the study. For investigation and collection of data descriptive survey method was used to find out the relationship between emotional intelligence and stress. Emotional Intelligence Scale (EIS) developed by Anukool Hyde, Sanjyot Pethe, Upinder Dhar and Teacher Stress Scale by Smith was used. Analysis and Interpretation of the data was done with the help of t-test and product moment correlation. Significant difference between the Stress scores of high & low E.I. was calculated by t-test and relationship between E.I. & Stress was tested with the help of product moment correlation. After analysis it was found that teachers with high emotional intelligence experience low teacher stress. Thus, emotional intelligence was found to be helpful in reducing stress of teachers and enhancing their effectiveness in teaching.